Boron and Phosphors Distribution Equilibria among the Molten Si, Slag and Metal Phases - Kai Tang; Egil Krystad; Gabriella Trenell; Merete Tangstad (The Minerals, Metals and Materials Society, 2013)
"A new UMG-Si refining concept has been proposed in this paper. Liquid Si and another liquid metal phase (Me) were separated by the molten slag spontaneously based on their different physicochemical properties. Two metal/slag distribution reactions are able to occur in the system simultaneously. Experimental investigation on the B and P distribution equilibria among Si/slag/Me was carried out in the graphite resistance furnace under the inert atmosphere. The B and P doped silicon was in equilibrium with either the SiO2-CaO or SiO2-CaO-l0%CaF2 slags at 1600 and 1650°C, respectively. The pure Fe and Cu metals were used in order to ""capture"" B and P in the slag phases. B and P in samples were determined by the ICP-MS. B and P distribution coefficients for the Si/slag/Me equilibria were compared with the theoretical calculations. The possible kinetic barriers for the Si/slag/Me three-layer equilibria have been analyzed. The metal contaminations in the three-layer equilibria were also examined. The present study provides a new approach for the refining of MG-Si.IntroductionMost of the impurities in the metallurgical silicon (MG-Si) are rather ""dilute'', ranging from few to several thousand ppms. However, the target impurity levels for upgrade metallurgical silicon (UMG-Si) feedstock are often far below the level of ppm. In such extreme case, the conventional refining technologies face the great technical challenges. B removal by slagging has already been implemented industrially. Removal of Pis frequently carried out by the vacuum distillation. The separating treatments for B and P removals lead to increase refining cost, total CO2 emission and longer pay-back time of solar cell module.It is well known that the phosphate capacities of slags in equilibrium with liquid silicon are extremely lower. However, if we introduce another phase that possesses high ""phosphor capacity"" into the Si/slag system, one would expect to continuously remove P from Si through molten slag to the new ""phosphor capturer"". The so-called three-layer refming concept is thus proposed in the present study. Liquid Si and another liquid phase (Me) are separated by the molten slag spontaneously based on their different physicochemical properties. Two metal/slag distribution reactions are able to occur in the system simultaneously."